Crisis Management in the Context of the COVID-19 Pandemic: The Municipality Council of Zliten as a Model - Khalil, Fatima Ali; Wali, Taha Muhammad (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
This study aims to shed light on some successful experiences in managing health crises, and to assess the extent to which they benefit from them in the Libyan case, as well as to identify the extent to which the Zliten Municipal Council can manage crises that can occur in general and the Corona crisis in particular. The descriptive analytical approach is used in the study. As for the conclusion of the study, it is that the crisis committee in the municipality of Zliten was not fully prepared to confront the Corona virus. This recommends the need to develop a special law regulating crisis management in the Libyan state and the establishment of a special body or ministry for crises within the ministries of the Libyan government, and that the municipality of Zliten work on the establishment of an emergency and crisis management center in the municipality.